Study of sex predominance in skin disorders in children aged 1 month to 5 years - Dr. Saiprasad Onkareshwar Kavthekar; Dr. Ashok Annasaheb Chougule; Dr. Anil Bapurao Kurane; Dr. Swati Saiprasad Kavthekar (Pediatric Review: International Journal of Pediatric Research, 2018)
Introduction: Skin diseases are common in children.Certain skin disorders show striking differences between sexes in incidence pattern.This study was undertaken to study the sex predominance of various skin disorders in children, aged 1 month to 5 years.Materials and Methods: 450 children aged between 1 month to 5 years attending Outpatient, Department of Pediatrics, D. Y. Patil Medical College and Hospital duringthe period of 1st September 2017 to 31St August 2018 included in this study.Age, sex and detailed history of all children were recorded. Skin examination was done under adequate illumination. Skin disorders were groupedunder 12 groups by clinical examination diagnosis. The data was analyzed statistically.Results: Maximum children of skin disorders belonged to age group 4-5 years and males 237(52.66%) outnumbered females 213(47.34%).Highest incidence was infections 254(56.44%). Out of infections, 95 with bacterial, 72 viral, 47 fungaland 40 parasitic infestations, males were 60(63.16%), 50(69.45%),12(25.54%), 25(62.5%) and females were 35(36.84%), 22(30.55%), 35(74.46%),15(37.5%) respectively. Forallergic disorders (38) and eczematouslesions (36) males were 28(73.68%), 20(55.55%) respectively while females were 10(26.32%), 16(44.45%) respectively. Congenital malformations (20) had 6(30%) males and 14(70%) females. Papulosquamous (26) and vesiculobullous (18) lesions had 8(30.77%) and 8(44.44%) males and 18(69.23%),10(55.56%)females respectively. Nutritional deficiency (18) and pigmentary lesions (20) were common in females 12(66.67%) and16 (80%) respectively.Conclusion: Bacterial, viral infections, parasitic infestations and allergic disorders showed significant sex predominance in males whereas fungal infections, congenital malformations, papulosquamous disorders, nutritional deficiency and pigmentary lesions significantly in females.